The winter soldier [compact disc, unabridged] - Mason, Daniel (Daniel Philippe) (Hachette Book Group, 2018)
Lucius, a young Viennese medical student, enlists, hoping to serve at a field hospital in the first World War. But he finds a freezing outpost the other doctors have fled. A single nurse remains, and Lucius has never lifted a scalpel. When an unconscious soldier is brought in from the snow, his uniform stuffed with strange drawings Lucius makes a fateful decision that will change lives forever.